To understanding of the burden of proof in Anglo-American law - Tiaglo, O. V.; Тягло, О. В.; ORCID: http://orcid.org/0000-0003-0721-1153 (Форум права = Forum Prava. – 2019. – Suppl. – P. t46-t53, 2019)
The translation into English of the original article published in Ukrainian Tiaglo, A. V. (2019). Forum Prava, 54(1). 69–76. DOI: http://doi.org/10.5281/zenodo.2563155.

З метою експлікації засобів розуміння і вираження тягаря доведення в англо-американському праві проведено порівняльний аналіз аналогічних фрагментів низки видань юридичного словника Блека. З’ясовано сукупність понять і відповідних термінів, в яких розуміється та висловлюється тягар доведення. Показано, що вона сформувалась і розвивається у логічному, риторичному та юридичному вимірах. Висунуто припущення, що це стосується усіх елементів кластера понять, в яких мислиться юридичне доведення, включно з поняттям доведення поза розумним сумнівом. Багатомірність даного поняття виступає, ймовірно, одним з істотних джерел відомого утруднення уніфікації практичного роз’яснення і використання стандарту доведення поза розумним сумнівом.

In order to explicate understanding and verbal expression of the burden of proof in English and American law the comparative analysis of similar fragments from few editions of the Black's law dictionary is fulfilled. First, set of concepts and corresponding terms by which the burden of proof is understood and expressed is found out. Omitting analogous ones, it is appropriate to restrict the subset of terms, on the one hand, by "belief" or "(legal) truth", "burden of persuasion", "risk of nonpersuasion", and, on the other hand, "burden of production" or "burden of going forward with the evidence", "prima facie case" and "order of proof". Second, particular understanding and expression of the burden of proof vary greatly depending on recognition of one or other legal standard of proof. Third, understanding of the burden of proof has evolved and functions now in at least three dimensions: legal, rhetorical, and logical. Fourth, it seems possible to extrapolate the conclusion about legal-rhetorical-logical multidimensionality of concept of the burden of proof to entire cluster of concepts (and terms) which grasps legal proof, including concept of proof beyond a reasonable doubt. But if so, then any attempt to reduce definitions of elements of this cluster, in particular – of concept of proof beyond a reasonable doubt, to pure logical definitions will be unsuccessful in general case. The multidimensionality of concept of proof beyond a reasonable doubt seems to be a significant source of well-known difficulty to unify practical explanation and use of the standard of proof beyond a reasonable doubt.

С целью экспликации средств понимания и выражения бремени доказательства в англо-американском праве проведен сравнительный анализ аналогичных фрагментов ряда изданий юридического словаря Блэка. Установлена совокупность понятий и соответствующих терминов, в которых понимается и выражается бремя доказательства. Показано, что она сформировалась и развивается в логическом, риторическом и юридическом измерениях. Выдвинуто предположение, что это касается всех элементов кластера понятий, в которых мыслится юридическое доказательство, включая понятие доказательства вне разумного сомнения. Многомерность данного понятия выступает, видимо, одним из существенных источников известной трудности унификации практического разъяснения и использования стандарта доказательства вне разумного сомнения.
К пониманию бремени доказательства в англо-американском праве
Tiaglo, A. V. To understanding of the burden of proof in Anglo-American law [Electronic resource] / A.V. Tiaglo // Форум права = Forum Prava. – 2019. – Suppl. – P. t48-t53. – Access mode: http://forumprava.pp.ua/files/048-053-2019-Suppl-FP-Tiaglo_8.pdf.
Tiaglo, A. V. (2019). To Understanding of the Burden of Proof in AngloAmerican Law. Forum Prava, 59(Suppl.). t48–t53. DOI: http://doi.org/10.5281/zenodo.3568265.
Keywords: Філософія. Логіка. Philosophy. Logic. Философия. Логика; Держава і право. State and Law. Государство и право; Наукові публікації. Scientific publications. Научные публикации; юридическая логика; юридична логіка; legal logic; доказательство; юридическое доказательство; бремя доказательства; доказательство вне разумного сомнения; англо-американское право; Юридический словарь Блэка; доведення; юридичне доведення; тягар доведення; доведення поза розумним сумнівом; англо-американське право; Юридичний словник Блека; proof; legal proof; burden of proof; proof beyond a reasonable doubt; English and American law; Black’s Law Dictionary